Uji Aktivitas Anti Bakteri Ekstrak Patikan Kerbau (Euphorbia hirta L.) Terhadap Pertumbuhan Bakteri Penyebab Diare (Eschercia coli) - Harlis, Harlis (Biospecies, 2010)
Patikan kerbau (Eupobia hirta L.) contains some anti-diarrheal compounds or containanti-bacterial substances which are alkaloids, flavonoids and tannins. This study aims to determine theeffect of extract of patikan kerbau on the growth of bacteria causing diarrhea (E.coli). This researchtests phytochemical properties and examines inhibition zone (hallow zone). The design used wasCompletely Randomized Design (CRD) with six treatment of patikan kerbau extract (0 ppm, 1500 ppm,1750 ppm, 2000 ppm, 2250 ppm and 2500 ppm) and four replications. Data were analyzed by usingANOVA and if there is a significant difference, the test will be followed by a DNMRT test at 5%significance level. Phytochemical test was based on the formed color intensity. The results showedthat - average inhibition zone diameter on treatment 2500 ppm with a diameter of 10.75 mm was notsignificantly different from 2250 ppm treatment with diameter of 9.75 mm. However, it wassignificantly different with treatments of 2000 ppm, 1750 ppm, 1500 ppm and control. The controlgroup (0 ppm) with a diameter of 6 mm (no inhibition zone formed) was significantly different fromother treatments. Phytochemical test showed that the active compound contained in patikan kerbauare alkaloids, flavonoids and tannins. These compounds have anti-bacterial property and can be usedas an anti-bacteria.